Могильники VIII – начала X вв. в Крыму - Айбабин, А.И. (Материалы по археологии, истории и этнографии Таврии, 1993)
В данной работе предпринята попытка систематизировать инвентарь погребений VIII—IX вв. и обосновать его более детальную периодизацию. Till recently in many works Byzantine buckles and decorations from the Crimea were dated by rather a large period: the 5th — 7th cent., the 6th — 8th cent., the 8th — 10th cent., and decorations typical for the Saitovo culture by the 6th — 7th or tlie 8th cent. In the same publications many stone graves found in the Crimea were synchronized with the graves of the same type from the upper layer of Suuk-Su burial in Gurzuf; N. I. Repnikov dated them back to the 9th — 10th centuries. New materials of the 8th — 9th centuries were published in 1960s — 1980s.